Eco-epidemiological aspects of Trypanosoma cruzi, Trypanosoma rangeli and their vector (Rhodnius pallescens) in Panama Generalidades do Trypanosoma cruzi, do Trypanosoma rangeli e do seu vetor (Rhodnius pallescens) no Panamá - Ana Maria de Vasquez; Franklyn E. Samudio; Azael Saldaña; Hector M. Paz; José E. Calzada (Revista do Instituto de Medicina Tropical de São Paulo, 2004)
The eco-epidemiology of T. cruzi infection was investigated in the Eastern border of the Panama Canal in Central Panama. Between 1999 and 2000, 1110 triatomines were collected: 1050 triatomines (94.6%) from palm trees, 27 (2.4%) from periurban habitats and 33 (3.0%) inside houses. All specimens were identified as R. pallescens. There was no evidence of vector domiciliation. Salivary glands from 380 R. pallescens revealed a trypanosome natural infection rate of 7.6%, while rectal ampoule content from 373 triatomines was 45%. Isoenzyme profiles on isolated trypanosomes demonstrated that 85.4% (n = 88) were T. cruzi and 14.6% (n = 15) were T. rangeli. Blood meal analysis from 829 R. pallescens demonstrated a zoophilic vector behavior, with opossums as the preferential blood source. Seroprevalence in human samples from both study sites was less than 2%. Our results demonstrate that T. cruzi survives in the area in balanced association with R. pallescens, and with several different species of mammals in their natural niches. However, the area is an imminent risk of infection for its population, consequently it is important to implement a community educational program regarding disease knowledge and control measures. A epidemiologia da infecção do T. cruzi foi investigada na margem oriental do canal do Panamá, na região central da Republica do Panamá. A informação obtida durante o estudo avaliou fatores de risco da doença de Chagas nesta área. Entre 1999 e 2000, 1110 triatomíneos foram coletados: 1050 triatomíneos (94,6%) em palmeiras, 27 (2,4%) em habitats periurbanos e 33 (3,0%) no interior de casas. Todos os espécimens foram identificados como R. pallescens. Não havia nenhuma evidência de domiciliação do vetor. O exame de glândulas salivares de 380 R. pallescens revelaram taxa de infecção natural por Trypanosoma de 7,6%, mas o conteúdo da ampola rectal de 373 triatomíneos mostrou 45% de positividade. Os perfis de isoenzimas em Trypanosomas isolados demonstraram que 85,4% (n = 88) eram T. cruzi e 14,6% (n = 15) eram ...